Perceived psychological stress and risk of herpes zoster: a nationwide population‐based cohort study. (7th May 2021) - Schmidt, S.A.J.; Sørensen, H.T.; Langan, S.M.; Vestergaard, M.
Summary: Background: Psychological stress may reduce cellular immunity, but its role in triggering latent infections, including herpes zoster (HZ), is controversial. Objectives: To examine the association between perceived psychological stress and risk of HZ. Methods: In a linked registry‐based cohort study, we followed 77 310 persons aged 40 years or older who participated in the 2010 Danish National Health Survey from 1 May 2010 until HZ diagnosis, death, emigration or 1 July 2014, whichever occurred first. We computed hazard ratios (HRs) of HZ associated with Cohen's Perceived Stress Scale (PSS) score (range 0–40) using Cox regression with age as the timescale, adjusted for sex, immunosuppressive and selected chronic conditions, immunosuppressive drugs, and sociodemographic, lifestyle and anthropometric factors. The PSS measures chronic stress perceived by an individual in response to various demands of daily life. We modelled the PSS score using quintiles and a restricted cubic spline function. Results: The unadjusted rate of HZ varied from 5·53 to 7·20 per 1000 person‐years from the lowest to the highest PSS score quintile. Compared with the lowest PSS score quintile, the adjusted HR for HZ was 1·00 [95% confidence interval (CI) 0·86–1·16], 1·08 (95% CI 0·92–1·26), 1·05 (95% CI 0·90–1·23) and 1·14 (95% CI 0·97–1·34) for the second to the fifth quintile, respectively. In cubic spline analyses, PSS scores < 20 were not associated with increased HR of HZ, but thereafter the HR increased linearly from 1·10 (95% CI 0·85–1·41) to 2·22 (95% CI 1·32–3·75). Conclusions: Our study indicated that high levels of psychological stress are associated with increased risk of HZ. Abstract : What is already known about this topic? Psychological stress may reduce cellular immunity, but its role in triggering latent infections, such as herpes zoster (HZ), is controversial. Previous epidemiological studies have mainly focused on the effects of negative life events (e.g. bereavement) on HZ risk, and dose–response analyses are lacking. It is possible that the allostatic load (the cumulative 'wear and tear' on the body associated with stress) depends on the type of stress and coping mechanisms. What does this study add? In this large population‐based cohort study, we found that persons reporting the highest levels of perceived psychological stress in daily life had an increased risk of HZ. Perceived psychological stress may be a modifiable risk factor for HZ. Our study adds HZ to the growing list of potential negative health consequences of psychological stress and underscores the importance of supporting mental wellbeing and resilience in the general population. Linked Comment: A.W.M. Evers and S. van Beugen. Br J Dermatol 2021; 185 :12–13 .